Short-term Outcomes for Patients and Providers After Elective Tracheostomy in COVID-19–Positive Patients - Murphy, Patrick (J Surg Res, 2021)
BACKGROUND: Urgent guidance is needed on the safety for providers of percutaneous tracheostomy in patients diagnosed with COVID-19. The objective of the study was to demonstrate that percutaneous dilational tracheostomy (PDT) with a period of apnea in patients requiring prolonged mechanical ventilation due to COVID-19 is safe and can be performed for the usual indications in the intensive care unit. METHODS: This study involves an observational case series at a single-center medical intensive care unit at a level-1 trauma center in patients diagnosed with COVID-19 who were assessed for tracheostomy. Success of a modified technique included direct visualization of tracheal access by bronchoscopy and a blind dilation and tracheostomy insertion during a period of patient apnea to reduce aerosolization. Secondary outcomes include transmission rate of COVID-19 to providers and patient complications. RESULTS: From April 6th, 2020 to July 21st, 2020, 2030 patients were admitted to the hospital with COVID-19, 615 required intensive care unit care (30.3%), and 254 patients required mechanical ventilation (12.5%). The mortality rate for patients requiring mechanical ventilation was 29%. Eighteen patients were assessed for PDT, and 11 (61%) underwent the procedure. The majority had failed extubation at least once (72.7%), and the median duration of intubation before tracheostomy was 15 d (interquartile range 13-24). The median positive end-expiratory pressure at time of tracheostomy was 10.8. The median partial pressure of oxygen (PaO2)/FiO2 ratio on the day of tracheostomy was 142.8 (interquartile range 104.5-224.4). Two patients had bleeding complications. At 1-week follow-up, eight patients still required ventilator support (73%). At the most recent follow-up, eight patients (73%) have been liberated from the ventilator, one patient (9%) died as a result of respiratory/multiorgan failure, and two were discharged on the ventilator (18%). Average follow-up was 20 d. None of the surgeons performing PDT have symptoms of or have tested positive for COVID-19. CONCLUSIONS: and relevance: PDT for patients with COVID-19 is safe for health care workers and patients despite higher positive end-expiratory pressure requirements and should be performed for the same indications as other causes of respiratory failure.